2011
DOI: 10.1128/aem.05212-11
|View full text |Cite
|
Sign up to set email alerts
|

Low Relative Abundances of the Mucolytic Bacterium Akkermansia muciniphila and Bifidobacterium spp. in Feces of Children with Autism

Abstract: Gastrointestinal disturbance is frequently reported for individuals with autism. We used quantitative real-time PCR analysis to quantify fecal bacteria that could influence gastrointestinal health in children with and without autism. Lower relative abundances of Bifidobacteria species and the mucolytic bacterium Akkermansia muciniphila were found in children with autism, the latter suggesting mucus barrier changes.Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder where gastrointestinal (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
264
5
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(308 citation statements)
references
References 27 publications
(27 reference statements)
11
264
5
8
Order By: Relevance
“…22,24 Finally, a novel mucin-degrading bacterium, Akkermansia muciniphila (phylum Verrucomicrobia), was found at a high level in children with AD by Finegold et al 19 Data regarding the gut microbiota are not always consistent, and some studies have described opposing results. 24 Indeed, some authors have found other genera (Sutterella and Desulfovibrio) in association with ASD patients, 19,25,26 and others have reported the absence of clinically meaningful differences in the intestinal microbiota composition of autistic patients.…”
Section: Dysbiosis In Asdsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,24 Finally, a novel mucin-degrading bacterium, Akkermansia muciniphila (phylum Verrucomicrobia), was found at a high level in children with AD by Finegold et al 19 Data regarding the gut microbiota are not always consistent, and some studies have described opposing results. 24 Indeed, some authors have found other genera (Sutterella and Desulfovibrio) in association with ASD patients, 19,25,26 and others have reported the absence of clinically meaningful differences in the intestinal microbiota composition of autistic patients.…”
Section: Dysbiosis In Asdsmentioning
confidence: 99%
“…22,24 Finally, a novel mucin-degrading bacterium, Akkermansia muciniphila (phylum Verrucomicrobia), was found at a high level in children with AD by Finegold et al 19 Data regarding the gut microbiota are not always consistent, and some studies have described opposing results. 24 Indeed, some authors have found other genera (Sutterella and Desulfovibrio) in association with ASD patients, 19,25,26 and others have reported the absence of clinically meaningful differences in the intestinal microbiota composition of autistic patients. 27,28 Further support for the microbial hypothesis and for a central role for the gut microbiota in AD derives from studies on autistic children who were treated with antibiotics; the results suggest that the clinical symptoms, regarding both gastrointestinal effects and cognitive skills, and the abnormal urinary secretion of certain chemical compounds may improve after antimicrobial treatment.…”
Section: Dysbiosis In Asdsmentioning
confidence: 99%
“…We were interested in contrasting urinary p-cresol levels in autistic and typically developing children because ASD has been associated with enhanced frequencies of (1) excessive gut permeability, reported by at least some (D'Eufemia et al, 1996;De Magistris et al, 2010), though not all studies (Robertson et al, 2008) and (2) gut infection with cresolproducing C. difficile (Finegold et al, 2002;De Angelis et al, 2013;Keşli et al, 2014;Selmer & Andrei, 2001;Wang et al, 2011). Our initial study reported significantly elevated amounts of urinary p-cresol in 59 Italian ASD children compared with 59 age-and sex-matched controls (p50.05) (Altieri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Total short-chain fatty acid (SCFA) levels as well as all individual SCFA, with the exception of caproic acid, and branched-chain fatty acids, were elevated in ASD subjects, pointing towards a general increase in microbiota population or activity rather than a major shift in composition, which would more likely lead to more specific changes in fermentation product profiles. The microbiota composition in the same study group had been determined previously [11], but the only significant differences found were a relative decrease in Akkermansia muciniphila and Bifidobacterium spp., with no changes in absolute levels of total bacteria. Also in this latest study [13], fecal levels of phenol and pcresol were determined as markers of amino acid metabolism; however, no differences were found between the study groups.…”
mentioning
confidence: 99%
“…A direct comparison between studies is complicated by the fact that different methodologies have been employed and that the study groups may not be directly comparable due to the heterogeneous nature of ASD (for example, ASD subjects with or without GI symptoms). Interestingly, non-autistic siblings of ASD subjects have often been found to have microbiota profiles intermediate between ASD and controls [8,10,11], possibly due to genetic factors, but also possibly a reflection of shared environmental conditions. These studies are further complicated by the fact that autistic subjects often receive frequent medication with antibiotics and are often on special diets or have repetitive dietary behaviors, both of which may alter microbiota composition.…”
mentioning
confidence: 99%